Peran Hukum Lingkungan Dalam Kerusakan Pengelolaan Lingkungan Hidup Di Indonesia - Arazid Arazid; Muhammad Yusuf Muda Azka; Andre Rizaldy; Irwan Triadi (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
The environment is a place where living things grow and develop including humans, therefore the environment needs to be considered properly and preserved. The purpose of this study is to determine the role of environmental law in environmental management in Indonesia. The method used in this writing is the normative juridical method, which is research aimed at finding and formulating legal arguments through analysis of the subject matter by conducting literature-based research and analyzing primary legal materials and secondary materials carried out by studying legislation and other literature in the form of books, journals, research results related to the problem, namely the Role of Environmental Law in Environmental Management Damage in Indonesia. Preventive environmental law enforcement aims to prevent environmental damage and/or pollution. Regulations regarding environmental protection and enforcement are contained in Law Number 32 of 2009. This law regulates the protection and management of the environment systematically to achieve environmental balance and human welfare as a unit.